Evaluation of varieties and hybrids of ensiled corn (Zea mays L.) - Fuentes, Jesús (2006)
This research was conducted to evaluate 16 corn varieties cultivated for silage. The evaluation included: fodder production of green and dry matter, protein content and in vitro dry matter digestibility (IVDMD) and organic matter digestibility (IVOMD). A completely randomized design was used for statistical analysis and Tukey mean separation was used when appropiated. Fodder production as kg/ha was higher for AN446 (114028), AN445 (110993), and AN430R (106389). Dry matter fodder production was higher for AN447 (29270), AN461 (28026), VS373 (25434). Protein content (%) was higher for G4657 (7.58), AN388 (7.28), and AN448 (7.17). The best values for IVDMD (%)were for G1990 (69.14), AN446 (63.78), and AN430RR (63.50), while the higher values for IVOMD (%) were for G1990 (71.78), AN446 (65.20), and AN447 (65.12). Varieties AN446 and AN447 appeared frequently with the best values in the parameters evaluated, therefore, new research has to be performed with these varieties to confirm results found in this study.